(untitled) (Nexo Revista Científica, 2020)
The article explores the definition of «competition» through an analysis of existing interpretations in the scientific literature. The authors reviewed and creatively revised more than 15 existing author’s interpretations of this concept. The current approaches to the classification of competitions are systematized and creatively revised. On the example of a comparative table of classification approaches, the main classification features of competitions are revealed. The appropriateness of applying the concept of «competition» in children’s, school and student competitions, as well as the concept of «open competition» used in the procurement of goods, works, services to meet state and municipal needs, is considered. As a result, the revealed signs of the competition allow us to conclude the appropriateness of using this concept as a tool for the distribution of material goods. In this case, they differ only in the scale of this distribution. The article also explores the list of olympiads and other intellectual and (or) creative contests, events aimed at developing intellectual and creative abilities, abilities to engage in physical education and sports, interest in scientific (research), engineering, inventive, creative, physical culture and sports activities, as well as the promotion of scientific knowledge, creative and sports achievements, recommended by the Ministry of Education of the Russian Federation. As a result, the target audience of participants for whom contests are initiated has been identified.